A Nonterminal Equine Mandibular Model of Bone Healing. Issue 3 (25th September 2014) - Sarrafian, Tiffany L.; Garcia, Tanya C.; Dienes, Erin E.; Murphy, Brian; Stover, Susan M.; Galuppo, Larry D.
<x xml:space="preserve">Abstract</x> Objectives To develop a nonterminal large animal bone defect model for assessing the efficacy of regenerative and pharmacologic treatments designed to enhance bone healing. Study Design In vivo experimental. Sample Population Adult gelding horses (n = 6). Methods Under general anesthesia, using radiographic guidance, 13.5 mm diameter bilateral, full thickness mandibular defects were created in 6 horses using a custom surgical jig and coring bit. After 16 weeks, under general anesthesia, 23 mm diameter cores that encompassed the original healing defects and surrounding parent bone material were removed for evaluation. Oxytetracycline was administered 14 days before final core harvest to label bone‐forming surfaces. Healing was qualitatively assessed from decalcified hematoxylin and eosin (H&E) stained and undecalcified fluorescent labeled sections. Trabecular to cortical bone fraction (Tb.V/Ct.V), bone volume fraction (BV/TV), tissue mineral density (TMD), and apparent bone mineral density (aBMD) were quantified using microcomputed tomography and compared between left and right sides using Wilcoxon signed rank test. Results BV/TV was not significantly different between left and right‐sided defects. Bone deposition occurred centripetally from the border of the original defect, filling 67% ± 16% (SD) of the defect at 16 weeks. Conclusion This model has potential use for comparison of regenerative and pharmacologic products aimed to augment bone healing.